Criticism and tests of the Edinburgh poultry growth model - Ezeukwu, Godwin Chukwudozie (The University of Edinburgh, 1982)
The ability to predict responses caused by changes in production input factors is an important management strategy. When used for this purpose, response simulation models can have useful roles to play especially in the field of animal production. The Edinburgh Poultry Growth Model was developed with the objective of assisting the poultry nutritionist, breeder, adviser and poultry farmer in the making of management decisions in the areas of poultry growth, with special reference to broiler production processes, from the important variables of nutrition, genotype, temperature and husbandry. An attempt has been made in this dissertation to test the Edinburgh Poultry Growth Model and to critically assess its theoretical features and performance. The model was found to possess great potential in fulfilling the stated objectives. The responses from the majority of the variables were consistent with those found in the existing research literature. It was found to be highly flexible and stable in coping with all the variables. However, the model is at present too sensitive in its temperature aspects. The assumptions made to formulate the equations for the heat loss mechanism are not yet adequate for simulating the thermoregulatory activities of poultry. It is believed that the problem is due to an absence in the existing state of knowledge, of appropriate data which could incorporate the behavioural responses to temperature in animals under ad libitum feeding systems. If this aspect of the model could be improved upon, it would enhance its value as a computer program in the fields of poultry production, research and teaching.
Keywords: Annexe MSc Digitisation Project 2022 Block 47; Edinburgh Poultry Growth Model; Management decisions; Nutrition; Temperature sensitivity; Thermoregulatory activities